PENERBITAN DUA AKTA JUAL BELI TERHADAP TANAH YANG SAMA: PERSPEKTIF HUKUM DAN KODE ETIK - Yusmiati,; Daly Erni, (The Juris, 2021)
The relinquishment or transfer of land rights in relation to the transfer of land rights can be carried out by means of buying and selling, grants, exchange, entry in the company (inbreng) and other legal acts of transferring rights, except that the transfer of rights through auction can only be registered if it is proven by a deed. made by the authorized Land Deed Making Official according to the provisions of the applicable laws and regulations. The Camat or Village Head based on the provisions of Article 5 paragraph (3) letter a of Government Regulation Number 37 of 1998, is an official who can be appointed as a Temporary PPAT to make deeds in areas where there is not enough PPAT. Problems arise when the issuance of two deed of transfer of land rights which is carried out before the official making the land deed in this case the Camat and the Village Head on the same land object with different buyers. The research was conducted from the legal aspect and the PPAT code of ethics on the consequences for the PPAT, prospective buyers and/or potential sellers as well as the consequences for the resulting deed. The method used is a normative juridical research method, where researchers study the norms contained in the applicable laws and regulations through secondary data sources, namely data obtained from library materials related to the formulation of the problem.